Development of Learning Models for Post-Earthquake Elementary School Students: Preliminary Studies - Ucu Rahayu; Leonard R. Hutasoit; Mestika Sekarwinahyu; Tri Wahyuningsih; Dyah Aniza Kismiati; Danang Budi Setyawan; Dola Suciana (Jurnal Penelitian Pendidikan IPA, 2023)
Disasters including earthquakes can traumatize people, especially children. One of the impacts is impaired concentration, making it difficult for children to learn or study. Hopefully, the right learning model can help students continue to participate in learning and heal the trauma. To find out this learning model, it is necessary to carry out a process of characterizing students in post-disaster areas. Based on the results of questionnaires and interviews with teachers and students in post-disaster areas, it is known that some students are still experiencing trauma, as indicated by 51.80% of students still having difficulty concentrating on studying. It is also known that the learning style of most students is auditory because 91.10% of students learn happier when they hear the teacher telling stories. Furthermore, student’s learning styles are visual as shown by 83.90% of students enjoying reading, 80.4% of students enjoying seeing pictures, and 57.10% enjoying seeing animations. Judging from the tendency for collaboration, students prefer to study in groups. Based on these characteristics, students enjoy learning with active, interactive, and fun activities, so the AICEF learning model can be an alternative that can be used as a learning model for elementary school students in post-earthquake areas